Accumulated Seasonal and Annual Temperature Degrees in the Kingdom of Saudi Arabia - Mosleh, Mosleh (Al-Adab Journal, 2025)
The research is based on studying accumulated temperature degrees in the Kingdom of Saudi Arabia at seasonal and annual levels. It aims to estimate the accumulative temperature degrees for each season of the year's seasons and estimate them at the annual level. The research also aims to classify the accumulated seasonal and annual temperature degrees into groups using the cluster analysis method. In carrying out the research, data were gained on monthly temperature data at (16) climatic stations affiliated with the National Meteorological Center in the city of Jeddah. These data extend over a period of thirty years (1989 - 2018).The research highlighted many results, as the results showed that the highest accumulated seasonal temperature degree was 2877.3°C in Al-Ahsa station during summer, and the lowest degree was 401.7°C in Arar station during the winter. Also, the highest accumulated annual temperature degree was 9192.4°C in Mecca station, which is the only station whose degree exceeded 9000°C, while the lowest degree was 4801°C at Abha station. The differences in classification of accumulated temperature degrees between winter and summer seasons were very clear. Any group in the winter did not have stations in the same group in summer season, with the exception of Abha station, which indicates the large differences in the accumulated temperatures between the two solstices. Summer season recorded the highest average of accumulative seasonal temperature degrees, which is 2533.9°C, while winter season recorded the lowest average of these temperatures degrees, which is 997.3°C. With regard to standard deviation, winter season showed the highest standard deviation at 443°C, while autumn season showed the lowest standard deviation at 313.2°C. Regarding the average accumulative annual temperature degree and their standard deviation, the average was 7233.1°C, and the standard deviation was 1224.3°C.